Risk factors for recurrent seizures in children with febrile seizures - Novita Novita; Astri Pinilih; Zaleha Ulfa; Nina Herlina (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Febrile seizure is defined as a seizure occurring in children aged 6–60 months with fever ≥38°C without intracranial infection. It is most common in children under three years, with a global prevalence of 2–5% and up to 12% in Asia. Although generally benign, recurrent febrile seizures may increase the risk of epilepsy later in life. Purpose: This study aimed to determine the risk factors associated with recurrent febrile seizures in children. Method: An analytical observational study with a cross-sectional approach was conducted using medical records of children diagnosed with febrile seizures. Bivariate analysis with chi-square test was applied to examine the association between risk factors and recurrence. Results: Children aged <2 years had a 2.5-fold higher risk of recurrence. Low birth weight (<2500 g) increased the risk by 2.5 times. A family history of febrile seizures was identified as a strong predictor of recurrence. Additionally, seizure onset with body temperature >39°C raised the risk by 4.5-fold. Conclusion: Age, low birth weight, family history, and high fever at seizure onset were significantly associated with recurrent febrile seizures. Early identification of these risk factors is essential for prevention and parental education to minimize recurrence and long-term complications.